ANALYSIS OF LIQUIDITY, PROFITABILITY AND WORKING CAPITAL EFFICIENCY AT KPRI â€œMARDISANTOSAâ€ KEBUMEN - Widyasari, Widhi; Rodhiyah, Rodhiyah; Prihatini, Apriatni Endang (Jurnal Ilmu Administrasi Bisnis, 2012)
Koperasi Pegawai Republik Indonesia (KPRI) â€œMardisantosaâ€ is one entity that aims to improve the welfare of its members in Kebumen, its activities include the areas of loan, shops and photocopy services. Management tried to achieve a return in line with expectations, for that management needs to take proper discretion in investing the funds available so that they can achieve the expected liquidity and profitability, and ultimately be able to improve the efficiency of working capital. but in reality KPRI â€œMardisantosaâ€ have not been able to manage their finances efficiently. Based on these conditions, then conducted research on ratio analysis of liquidity, profitability and working capital efficiency at KPRI "Mardisantosa" period 2006-2010. Research objective is to determine the level of liquidity, profitability and efficiency of working capital at KPRI "Mardisantosa". The method used descriptive analysis of data retrieval in time series of the consolidated balance sheet income statement in the period 2006 to 2010, and the Annual Members Meeting report KPRI "Mardisantosa". Techniques of data collection is through secondary data and documentation. Other sources of data acquired from the KPRI "Mardisantosa". Data were analyzed quantitatively by using the liquidity ratio, profitability, working capital turnover ratio and working capital efficiency. Results showed that the ratios for five-year cooperative liquidity is relatively high. Achieved the highest liquidity ratio is 383.33% Current Ratio, Quick Ratio 314.33%, and Net Working to Total Assets amounted to 68.56%. Cooperative profitability ratio is relatively low over the past five years, the highest rate of return is achieved ROE of 6.84% and ROA of 3.41%, while the lowest is at 3.34% ROE and ROA of 1.83%. Net Working Capital Turnover cooperatives tend to be very low, for five years of Net Working Capital Turnover reached the highest cooperatives times are 1.37 and 0.55 times the lowest. There is excess working capital during the study period. During the five-year working capital turnover is relatively low and has a working capital surplus that indicate inefficient use of working capital. The conclusion of this study is that for five years the cooperative has a working capital surplus, or inefficient use of working capital. Liquidity during the five-year relative good enough so in adequate condition, in relatively low profitability and working capital turnover is relatively low so that the maximum profit is less cooperative and there have not been empowered working capital efficiently. The advice given is KPRI "Mardisantosa" need to seek working capital as required, control spending or operating expenses to gain more leverage.